Sources of Exchange Rate Fluctuation in Vietnam: An Application of the SVAR Model - Phuong, Nguyen Van (Asian Economic and Financial Review, 2015)
Vietnam has been implementing the export-oriented economy, in which the central bank of Vietnam, well-known as the State Bank of Vietnam (SBV), has adopted the managed float exchange rate regime since 1990. Therefore, the exchange rate movement plays an important role in stimulating the Vietnamese export activities. By using the long-run SVAR model, pioneered by Blanchard and Quah (1989), this study examines how the real and nominal shocks impact the nominal and real exchange rate (USD/VND) in Vietnam. We use monthly data on the USD/VND exchange rate, the price levels in Vietnam and the United States from May 1995 to December 2013. Our empirical results reveal that the real shock primarily leads the real and nominal exchange rate (USD/VND) to fluctuate over time. Meanwhile, the nominal shock has a temporary effect on the movement of the real exchange rate in Vietnam. Our research also finds that the long-run Purchasing Power Parity (PPP) does not hold in Vietnam.